Identification and Structure Prediction of Human Septin-4 as a Biomarker for Diagnosis of Asthenozoospermic Infertile Patients—Critical Finding Toward Personalized Medicine - Vickram, A. S.; Anbarasu, K.; Jeyanthi, Palanivelu; Gulothungan, G.; Nanmaran, R.; Thanigaivel, S.; Sridharan, T. B.; Rohini, Karunakaran (Frontiers in Medicine, 2021)
Semen parameters are been found as key factor to evaluate the count and morphology in the given semen sample. The deep knowledge towards male infertility will unravel with semen parameters correlated with molecular and biochemical parameters. The current research study is to identify the motility associated protein and its structure through in-silico approach. Semen samples were collected and initial analysis including semen parameters were analyzed by using WHO protocol. Semen biochemical parameters including seminal plasma protein concentration, fructose content, glucosidase content was calculated and evaluated for correlation. SDS-PAGE and MALDI-TOF was carried out for identification of Septin-4 presence in semen sample. Mascot search was done for protein confirmation and in-silico characterization of Septin-4 by structural modelling in I-TASSER. 25ns molecular dynamics simulations results showed the stable nature of Septin-4 in dynamic system. Overall, our results showed the presence of motility associated protein in normospermia and control sample and not in the case of asthenospermia and oligoasthenospermia. Molecular techniques characterized the presence of Septin-4 and as novel biomarker for infertility diagnosis.